KAJIAN KUAT TEKAN BETON KEKANG FC’30 DENGAN BAHAN TAMBAH GEOGRID (TERCATE) - Lubis, Rizki Adriansyah; Rosyad, Farlin (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Along with the development of the times, especially in the field of construction is currently developingquite rapidly, accompanied by the availability of various types of modern and practical materials, one of theconstruction materials that is often used in construction is concrete, almost every aspect of human life is alwaysrelated to concrete, both directly and indirectly, for example the relationship of human life directly or indirectlytoconcrete, namely,humansenjoyanduseconstructionsuchasroads,bridges, airports,breakwaters, anddamswhose structures are made of concrete. Concrete is in great demand because concrete has many advantages,including fire resistance, its components are easily obtained, and it has very high strength and bearing capacity,so that concrete can be applied to all building designs, meanwhile behind the advantages of concrete, althoughconcrete is able to withstand the load force well. the ability of concrete to withstand low tensile and compressivestress, the construction is easily cracked if it gets tensile and compressive stress, to anticipate this, the concreteis given additional reinforcement, the provision of reinforcement to this concrete beam is known as reinforcedconcrete.